Systematic selection of international markets using a hybrid multi-criteria approach: A study in the paper and paperboard industry - López-Cadavid, Diego Alejandro; Vanegas-López, Juan Gabriel; Restrepo-Morales, Jorge Anibal; Roldán-Sepúlveda, Mayerlín (Cogent business & management, 2023)
Internationalization makes possible the competitive development of firms. This study proposes a methodology for the selection of international markets that identifies the most favourable international destinations for the paper and paperboard export industry in Colombia. For this purpose, a set of 23 factors divided into 5 categories are defined through literature: costs, trade barriers, logistics, environment and culture, and economy. This comprehensive model is applied to a set of 15 exporting firms and a combination of the multi-criteria models Analytic Hierarchy Process (AHP), and Evaluation Based on Distance from Average Solution (EDAS) is used for its development. The results indicate that the priority factors when choosing an international market are import costs (0.1974), transit time (0.1392), transport frequency (0.1174) and international transport costs (0.0971). Also, considering these priorities, the most viable markets for companies in this sector are Netherlands (0.9894), the United Kingdom (0.9740), Belgium (0.9409) and Germany (0.9351). The results obtained represent the identification of new possible alternative markets for Colombian companies in the paper sector to expand their international reach and develop in significantly more attractive and convenient markets according to their priorities. Also, this article contributes significantly to the development of methodologies for international markets exploration.